The Relationship Between Brand Reputation and Risk Perception on Customer Purchasing Decisions on E-commerce Platforms - Suryati, Lili; Fenny, Fenny (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This study aims to analyze the effect of brand reputation on consumer risk perception and purchasing decisions on e-commerce platforms. Specifically, this study examines how brand reputation can reduce consumer risk perception and directly or indirectly drive purchasing decisions. The research method used is a quantitative approach with a survey of 200 e-commerce user respondents in Medan City. Data were analyzed using path analysis to test the relationship between variables, including the mediation effect of risk perception in the relationship between brand reputation and purchasing decisions. The results showed that brand reputation has a significant negative effect on consumer risk perception, meaning that the better the brand reputation, the lower the perceived risk perception. In addition, risk perception has a significant negative effect on purchasing decisions, where the higher the perceived risk, the lower the consumer's tendency to make a purchase. Brand reputation also has a significant positive effect on purchasing decisions, both directly and through the mediation effect of risk perception. These findings emphasize the importance of building and maintaining a strong brand reputation as a strategy to reduce consumer perceived risk and increase purchasing tendencies. The managerial implications resulting from this study are that e-commerce companies need to focus on managing brand reputation and efforts to reduce risk perception in order to encourage consumer trust and interest in transacting. This research makes an important contribution to understanding consumer behavior in the digital era and the factors that influence purchasing decisions in the context of e-commerce.